Adaptiveness changing earth system governance - Djalante, Riyanti 1977-; Siebenhüner, Bernd 1969- (Cambridge University Press, 2021)
Rapid and transformational actions are ever more urgently needed to achieve a just, resilient, and ecologically sustainable global society, as envisioned and supported by the Sustainable Development Goals. Moreover, dynamic governance approaches are vital for addressing changing and uncertain conditions. At many levels, governance needs to be responsive and flexible - in one word - adaptive. This book provides a state-of-the-art review of the conceptual development of adaptiveness as a key concept in the environmental governance literature, complemented by applications from global, regional, and national levels. It reviews the politics of adaptiveness, investigates which governance processes foster adaptiveness, and discusses how, when and why adaptiveness influences earth system governance. It is a timely synthesis for students, researchers and practitioners interested in environmental governance, sustainability and social change processes. This is one of a series of publications associated with the Earth System Governance Project. For more publications, see www.cambridge.org/earth-system-governance